Creation of Tissue-Engineered Urethras for Large Urethral Defect Repair in a Rabbit Experimental Model - Amesty, Maria Virginia; Chamorro, Clara Ibel; López-Pereira, Pedro; Martínez-Urrutia, María José; Sanz, Beatriz; Rivas, Susana; Lobato, Roberto; Fossum, Magdalena (Frontiers in Pediatrics, 2021)
Introduction: Tissue engineering is a potential treatment for severe and difficult urethral defects. Our aim was to create tissue-engineered urethras by harvesting autologous cells obtained by bladder washes and then using these cells for creating a functional neourethra in a chronical hypospadias rabbit model. Methods: A chronic hypospadias model was first created in male New-Zealand rabbits by resecting an elliptic defect (70mm2) in the ventral penile urethra and then letting it mature as an established defect for 5-6 weeks. Urothelial cells were harvested non-invasively by washing the bladder with saline and isolating the urothelial cells. Neo-urethras were created by seeding the urothelial cells on a commercially available decellularized intestinal submucosa matrix (Biodesign®Cook-Biotech®). Twenty-two rabbits were divided into 3 groups. Group-A (n=2) a control group (unrepaired hypospadias). Group-B (n=10) and group-C (n=10) underwent on-lay urethroplasty, with unseeded matrix (group-B); and urothelial cell-seeded matrix (group-C). Macroscopic appearance, radiology and histology was assessed. Results: The chronic hypospadias model was successfully created. Stratified urothelial cultures attached to the matrix were obtained. All group-A rabbits kept the urethral defect size unchanged (70±2.5mm2). All group-B rabbits presented urethroplasty dehiscence, with a median defect 61 mm2 (range 34-70). In group-C, 5 presented complete urethral correction, and 5 almost total correction with fistula, with a median defect of 0.3 mm2 (range 0-12.5), demonstrating a significant better result (p=7.85x10-5). Urethrography showed more fistulas in group-B (10/10, versus 5/10 in group-C) (p=0.04). No strictures were found in any of the groups. Group-B histology identified absence of ventral urethra in unrepaired areas, with squamous cell metaplasia in the edges towards the defect. In group-C repaired areas, ventral multilayer urothelium was identified with cells staining for urothelial cell marker cytokeratin 7. Conclusions: The importance of this study is that we used a chronical hypospadias animal model and clearly found that cell-seeded transplants were superior to non-seeded. In addition, bladder washing was a feasible way of harvesting viable autologous cells in a non-invasive way. There is a place for considering tissue engineered transplants in the surgical armamentarium for treating complex urethral and hypospadias cases.